How context affects transdisciplinary research: insights from Asia, Africa and Latin America - Flurina Schneider; Aymara Llanque-Zonta; Onintsoa Ravaka Andriamihaja; R. Ntsiva N. Andriatsitohaina; Aung Myin Tun; Kiteme Boniface; Johanna Jacobi; Enrico Celio; Clara Léonie Diebold; Laby Patrick; Phokham Latthachack; Jorge Claudio Llopis; et al. (Sustainability Science, 2022)
Transdisciplinary research (TDR) has been developed to generate knowledge that effectively fosters the capabilities of various societal actors to realize sustainability transformations. The development of TDR theories, principles, and methods has been largely governed by researchers from the global North and has reflected their contextual conditions. To enable more context-sensitive TDR framing, we sought to identify which contextual characteristics affect the design and implementation of TDR in six case studies in Asia, Latin America, and Africa, and what this means for TDR as a scientific approach. To this end, we distinguished four TDR process elements and identified several associated context dimensions that appeared to influence them. Our analysis showed that contextual characteristics prevalent in many Southern research sites—such as highly volatile socio-political situations and relatively weak support infrastructure—can make TDR a challenging endeavour. However, we also observed a high degree of variation in the contextual characteristics of our sites in the global South, including regarding group deliberation, research freedom, and dominant perceptions of the appropriate relationship between science, society, and policy. We argue that TDR in these contexts requires pragmatic adaptations as well as more fundamental reflection on underlying epistemological concepts around what it means to conduct “good science”, as certain contextual characteristics may influence core epistemological values of TDR.